Simplified 3D Printing Method for Fabrication of Superhydrophobic Oil–Water Separation Membrane With Controllable Pore Size - Wang, Xiaolong; An, Jingjing; Hassan, Alaa; Gao, Qingsen; Liu, Xianhu; Boudaoud, Hakim (Journal of Applied Polymer Science, 2025)
Efficient separation of oil/water mixtures is crucial amid increasing environmental challenges from industrial activities. In recent years, researchers have discovered that biomimetic hydrophobic materials hold significant potential for promising applications. However, existing technologies often use non-degradable materials and face challenges in structure design. This study explores how Fused Filament Fabrication (FFF) 3D printing can create PLA membranes with controlled pore sizes (minimum 313.02 μm) without complex modeling. In the subsequent modification process, a superhydrophobic nano-silica coating is easily applied via spraying, achieving a contact angle of 154.64°. The sample maintained its superhydrophobicity even after undergoing water jet impact and peeling cycles, demonstrating the stability of the coating. The modified membranes could achieve oil–water separation with a biggest flux of 81.89 mL cm−2 min−1 and over 90% efficiency in dichloromethane separation. This research highlights FFF's potential in sustainable oil/water separation, addressing current limitations and paving the way for eco-friendly separation technologies.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Applications; Biodegradable; Membranes